PSXIV-8 Performance of Nellore bulls fed probiotic (Saccharomyces cerevisiae boulardii CNCM I-1079) during adaptation in feedlot. (8th October 2021) - Bomfim, Lorena Emily L M; Nascimento, Kaique S; Couto, Victor R Moreira; Arnhold, Emmanuel; da R Fernandes, Márcia Helena M; Moura Silva, Luan O; Mari, Lucas José; Santos, Mateus Castilho; Gauthier, Marine; Chevaux, Eric; De Resende Fernandes, Juliano José
Abstract: This study aimed to evaluate the effect of probiotic (Saccharomyces cerevisiae boulardii CNCM I-1079) supplementation during feedlot adaptation period on performance of Nellore bulls. One-hundred ninety-eight Nellore bulls were used in a completely randomized block design, divided in 22 pens (9 animals/pen). Treatments were: CON – adaptation diet and finishing diet comprised of basal diet (with 28 ppm of monensin); and SCB – same diets as for the previous treatment with monensin plus probiotic (Saccharomyces cerevisiae boulardii CNCM I-1079, ProTernative ® 20; Lallemand Animal Nutrition at a dose of 1.0 x 10 e 10 cfu/animal/d) supplementation. Supplementation was offered for the first 42 days (21 days in the step-up phase and 21 days in the finishing diet with 900 g concentrate/kg DM), then both treatments were fed the same basal diet for another 76d, reaching 118 days in total. Pen was considered the experimental unit. Growth data were analyzed using the MIXED procedure of SAS with Tukey test at 5% significance level, and a linear regression analysis was performed for the dry matter intake (DMI) data. During the first 42 days, average DMI did not differ; however, bulls fed SCB plateaued the curve of at 9.17 kg DMI/d earlier (39 days, R 2 = 0.97) than those fed CON (43 days; R 2 = 0.96) diets. Final body weight (509.5 vs. 518.0 kg, P = 0.02), total body weight gain (163.7 vs. 170.3 kg, P = 0.01) and average body weight daily gain (1.366 vs. 1.420 kg, P = 0.01) were greater for SCB-fed bulls. Feed efficiency of SCB-supplemented bulls was 8.05% greater than CON (P = 0.04). Probiotic supplementation with live yeast Saccharomyces cerevisiae boulardii CNCM I-1079 during the first 42 days in feedlot contributes to reaching the plateau of DMI curve earlier and improving overall performance of Nellore bulls during the total period.